STRATEGI PENGELOLAAN KOMPONEN PEMBELAJARAN BAHASA ARAB - Fathur Rohman (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2014)
In the field of education, teaching management is one of the most important parts to ensure the success and the effectiveness of teaching. This article aims to describe the application of teaching management in the field of Arabic language teaching. The results presented in this article is that there are some aspects that need to manage in the field of teaching Arabic language, those are: curriculum, teaching materials, students, teachers, evaluation, teaching methods, and teaching purposes. DOI: 10.15408/a.v1i1.1131